A new species of Miroculis (Ephemeroptera: Leptophlebiidae) from NE Argentina - Dominguez, Eduardo (2007)
The genus Miroculis Edmunds has species described from Brazil, Colombia, Peru, Venezuela and Suriname, with additional records from other countries in northern South america. In this paper, Miroculis (Ommaethus) misionensis sp. nov. is described from male and female imagos from Misiones Province, NE Argentina. This constitutes the Southernmost record for the genus.